2022
DOI: 10.1186/s12935-022-02776-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a risk prediction model for overall survival in patients with nasopharyngeal carcinoma: a prospective cohort study in China

Abstract: Objective Nasopharyngeal carcinoma (NPC) is prevailing in Southern China, characterized by distinct geographical distribution. Aimed to predict the overall survival (OS) of patients with nasopharyngeal carcinoma, this study developed and validated nomograms considering demographic variables, hematological biomarkers, and oncogenic pathogens in China. Methods The clinicopathological and follow-up data of the nasopharyngeal carcinoma patients obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Previous researches showed that LAR was significantly related to a relatively short OS and PFS in NPC. 41 , 42 These findings illustrated the adverse effects of nutritional deficiencies on survival of patients with NPC and the importance of nutritional interventions.…”
Section: Discussionmentioning
confidence: 89%
“…Previous researches showed that LAR was significantly related to a relatively short OS and PFS in NPC. 41 , 42 These findings illustrated the adverse effects of nutritional deficiencies on survival of patients with NPC and the importance of nutritional interventions.…”
Section: Discussionmentioning
confidence: 89%
“…A deeper analysis of existing survival predictors reveals that among the 74 studies 54 utilized publicly accessible data from three key databases: the Cancer Genome Atlas Program (TCGA) 17 , NCI Genomic Data Commons (GDC) 18 , and the Gene Expression Omnibus (GEO) 31, 32, 72, 73, 80, 82, 87, 90, 91, 130, 131 . Apart from public databases, there also exist private databases that have been utilized in existing survival prediction studies 66,75,81,112,113,117,118 . However, these private databases often restrict data access and may require extensive research proposals for data retrieval.…”
Section: Resultsmentioning
confidence: 99%
“…Table 8 provides information about 44 diseases and the corresponding survival prediction algorithms utilized in these diseases. A deeper analysis of Table 8 shows that Cox-PH and lasso Cox-PH models have been extensively utilized for disease specific survival prediction i.e., ASCVD 29,111 , bladder cancer 40,82 , colorectal cancer 7477 , hepatocellular carcinoma 43,86,87 , ovarian cancer 88–90,103 , lung adenocarcinoma 101 , heart failure 118 , HER2-negative metastatic breast cancer 67 , pancreatic cancer 26,71 , trauma 120 , nasopharyngeal carcinoma 66 , triple-negative breast cancer 68 , lymphoma 85 , breast cancer 40,81,82 , ovarian cancer 88–90,103 , and lower-grade glioma 80 , cardiovascular disease 112,114117 , invasive ductal carcinoma 70 , liver transplantation 119 , gastric cancer 42 , lung cancer 27 , esophageal squamous cell carcinoma 79 , glioma 69 , and liver cancer 41 . RSF has been employed in 13 studies for 6 diseases namely, ASCVD 29 , bladder cancer 82 , gastrointestinal cancer 30 , cervical cancer 73 , liver transplantation 119 , and heart failure 118 .…”
Section: Resultsmentioning
confidence: 99%
“…In fact, a few composite hematological indexes have been proposed in some studies; for example, Chen et al 26 and Zhou et al 28 used high-density lipoprotein cholesterol, apolipoprotein A-1, EBV VCA-IgA, and EA-IgA and Xiang et al 27 Nomograms are widely used for cancer prognosis, primarily because of their ability to reduce statistical predictive models into a single numerical estimate of the probability of an event, such as death or recurrence. [17][18][19][20][21][22][23][24][25][26][27][28] In our study, nomogram_CHS was constructed based on MVA results (Node classification, chemotherapy (yes/no), EBV-DNA, and CHS). The nomogram_CHS had better prognostic efficiency than TNM-8 with a higher C-index in the training (0.728 vs 0.646) and validation cohort (0.893 vs 0.622).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27][28] However, most of these previous studies had some shortcomings, such as (1) including some unconventional biomarkers, [19][20][21][22][23][24][25][26] (2) not considering hematological and clinical measures when constructing the nomogram, 17,18 and (3) not integrating these measures to construct a composite signature to guide the clinical decision-making process. [17][18][19][20][21][22][23][24][25][26] Therefore, this study aimed to evaluate the prognostic and predictive value of a circulating hematological signature (CHS), which was constructed using a panel of indicators of inflammation, nutrition, and coagulation biomarkers. The CHS was then utilized to develop a potential prognostic model for predicting distant metastasis-free survival (DMFS) and OS in patients with non-metastatic NPC to guide individualized treatment.…”
Section: Introductionmentioning
confidence: 99%